Factors of Professional Elicitation of Unemployed Over 50 Years Old in Poland - Adam P. Balcerzak; Dominik Sliwicki (Institute of Economic Research (IER), 2013)
The end of the first decade of the XXI century is currently seen mostly from the perspective of global financial crisis that resulted in serious economic downturn in real sphere. The financial markets instability, public finance problems, GDP stagnation and, in the end, recession seriously increased the problem of unemployment in many European countries. However, today when one looks at European labour markets from a longer perspective, one can see that the Union faces much more fundamental problems than the current economic disturbances. The process of population ageing raises economic challenges that will probably affect European growth, the future international position of the European Union and, in the end, it will affect the living standard of all European citizens. The process of ageing population, with all its negative consequences, is going to be an especially important problem for the Polish economy. The financial and organizational burden of growing number of older dependents, in the reality of one of the lowest level of labour markets participation in European Union, is especially threatening for the Polish growth perspectives and the fiscal sustainability of the country. The policy makers must form strategies that could improve the demographic situation and lower the dependency ratios (the ratio of inactive population as a percentage of employed population). The problem of low labour market participation, especially in the segment of population above 50 years old, is already a serious burden for the Polish development. The above mentioned ageing process is going to make it even worse. As a result, the aim of this chapter is to find the factors that influence professional elicitation of unemployed people over 50 years old in Poland. This knowledge is the starting point for forming labour market policies that can be helpful in facing current and medium-term problems but also, it is essential for thinking about long term strategies. The chapter consists of three parts and is organized as follows. In the first part, the data concerning the current demographic situation of Europe and its long term projections is presented. This subchapter also touches upon the issue of macroeconomic financial consequences of the ageing process in Europe. In the second part of the chapter, some best practices of the Netherlands and Finland are presented. In the last subchapter the empirical logit analysis for Poland is conducted.
Keywords: 330; labour markets; Unemployed over 50 year-old